Fixed Point Theorems and Asymptotically Regular Mappings in Partial Metric Spaces. (23rd May 2013) - Shukla, Satish; Altun, Ishak; Sen, Ravindra
Abstract : The notion of asymptotically regular mapping in partial metric spaces is introduced, and a fixed point result for the mappings of this class is proved. Examples show that there are cases when new results can be applied, while old ones (in metric space) cannot. Some common fixed point theorems for sequence of mappings in partial metric spaces are also proved which generalize and improve some known results in partial metric spaces.